A Simulation-Based Study of Dorsal Cochlear Nucleus Pyramidal Cell Firing Patterns - Mohammad Reza Daliri; Zahra Daneshparvar (Basic and Clinical Neuroscience, 2012)
A two-variable integrate and fire model is presented to study the role of transient outward potassium currents in producing temporal aspects of dorsal cochlear nucleus (DCN) pyramidal cells with different profiles namely the chopper, the pauser and the buildup. This conductance based model is a reduced version of KM-LIF model (Meng & Rinzel, 2010) which captures qualitative firing features of a detailed physiological model (Kanold & Manis, 2000).For our development we benefit from transient potassium currents properties i.e.fast activation and slow inactivation to generate long latency before start of firing.We compare our minimal model outputs in response to a hyperpolarizing stimulus fallowed by a depolarizing one with the data of KM-LIF model.The results conform well to the KM-LIF model with lower complexity.